2015
DOI: 10.1142/s2047684115500116
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modeling of non-woven fiber mats: Their effective mechanical and electrical properties

Abstract: Numerical simulations on non-woven-fibrous, porous structures were performed to determine material design space for energy storage device (battery and ultracapacitor) separators. Material simulations were performed initially with a commercial program called GeoDict using its demo version. Later, in-house computational tools were developed and employed. The numerical routines were created to model mechanical and electrical properties of porous structures. The tools were built as a preprocessor for a commercial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Due to the different simulating and hardware configuration of the workstations, the specific simulation strategy should be determined also according to the actual situation. For simulation experiments where the accuracy requirements are not very high, following simulation conditions are also worth recommending due to low computational cost: Length of the fibers as variable and radius fixed as constant Box size = 450 um Periodic boundary conditions…”
Section: Resultsmentioning
confidence: 99%
“…Due to the different simulating and hardware configuration of the workstations, the specific simulation strategy should be determined also according to the actual situation. For simulation experiments where the accuracy requirements are not very high, following simulation conditions are also worth recommending due to low computational cost: Length of the fibers as variable and radius fixed as constant Box size = 450 um Periodic boundary conditions…”
Section: Resultsmentioning
confidence: 99%
“…These results were compared with two experimental data and analyzed with a high degree of accuracy. Enis Tuncer et al [97] also use GeoDict for the optimization of porosity with respect to mechanical and electrical properties. It was concluded that the best range for the required properties is between 0.4- GeoDict generates a 3D model using several inputs.…”
Section: Geodictmentioning
confidence: 99%
“…Only a few, for instance, the McLachlan equation, can mathematically describe the conductivity over the whole range of possible filler fractions. Additionally, many modeling works have also been suggested to describe the conductivity properties, which have been summarized by Thomassin et al quite well. However, it must be noted that nonanalytical simulation methods, for instance, when Monte Carlo generated model composites are analyzed with either finite element modeling (FEM) or electrical network methods, can, to some extent, also be used to predict the conductivity both below and above the percolation threshold.…”
Section: Introductionmentioning
confidence: 99%